2016
DOI: 10.1080/21505594.2015.1112491
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene disruption in Candida parapsilosis demonstrates a role for CPAR2_404800 in adhesion to a biotic surface and in a murine model of ascending urinary tract infection

Abstract: Candida parapsilosis is an emerging opportunistic pathogen, second in frequency only to C. albicans and commonly associated with both mucosal and systemic infections. Adhesion to biotic surfaces is a key step for the development of mycoses. The C. parapsilosis genome encodes 5 predicted agglutinin-like sequence proteins and their precise role in the adhesion process still remains to be elucidated. In this study, we focused on the putative adhesin Cpar2_404800, in view of its high homology to the most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 43 publications
5
53
0
1
Order By: Relevance
“…A role for CpAls7 in adhesion was first suggested by a study showing that the protein was isolated from a fibronectin affinity column (17). Another study showed that a strain deficient in CpALS7 had reduced adhesion to buccal epithelial cells in vitro and a reduction in the fungal burden in a mouse model of urinary tract infection (19). Our study provides additional evidence to support a role for CpAls7 in adhesion.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A role for CpAls7 in adhesion was first suggested by a study showing that the protein was isolated from a fibronectin affinity column (17). Another study showed that a strain deficient in CpALS7 had reduced adhesion to buccal epithelial cells in vitro and a reduction in the fungal burden in a mouse model of urinary tract infection (19). Our study provides additional evidence to support a role for CpAls7 in adhesion.…”
Section: Discussionsupporting
confidence: 71%
“…Yeast cells that contained the vector without CpALS7 showed minimal adhesion regardless of the carbon source. To further investigate the effect of CpALS7 on adhesion, a CpALS7 deletion strain (KO) (19) and its wild-type parent (ATCC 22019) were tested in the adhesion assay ( Fig. 7B).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Bertini et al 13 highlights the need for more detailed investigations of one of the most important features of the pathogenesis program by fungi-the adhesion to host tissues and cells-not only in C. albicans but in other emerging Candida pathogens. There are several reports about the different adhesion capacities for individual Candida species, including C. parapsilosis.…”
mentioning
confidence: 99%
“…13 The authors identified and disrupted a hypothetical, adhesion effecting gene "CPAR2_404800," (ortholog of C. albicans ALS genes), using a previously described gene deletion method.…”
mentioning
confidence: 99%